Bahaghari't bulalakaw : katipunan ng mga sanaysay at mga pag-aaral - Agoncillo, Teodoro A. 4 0 16; 5 (Quezon City, Philippines : University of the Philippines Press, 1998)
Literary criticism on the character in Philippine writings.
In Tagalog.
Keywords: 2 -- 0; 6; History and criticism.;History and criticism. -- Philippine literature (English);Short stories, Philippine;Characters and characteristics in literature. -- 20; 20; 2